Establishing Mobile Learning Elements using Competency-Based Education Framework - Abdullah, Siti Azwanee; Saud, Muhammad Sukri; Mohd Hisham, Mohd Hizwan (Journal of Technical Education and Training, 2021)
The development of wireless and mobile technologies has contributed to the use of mobile devices as a teaching medium in teaching and learning process. Mobile Learning or M-Learning is a recent E-Learning environment. Unlike traditional learning settings, it has been introduced as a digital learning technology leading to new types of learning through the availability of mobile devices. The purpose of this study is to explore Mobile Learning elements based on Competency-Based Education (CBE) in Technical and Vocational Education (TVET) field. A qualitative study has been done on the six experts which were an expert in Competency Based Education field. The experts were chosen based on specific qualities to obtain the most relevant data via semi-structured interview. The transcribed interview data were analyzed by using thematic analysis using Atlas.ti software to produce elements and matrix tables related to appropriate elements. Based on the qualitative results, eight elements were formed: students, teachers, content, learning design, learning activity, learning environment, technology and assessment. The study generates the implementation framework to utilize the mobile device as a supporting element in teachers instruction and to improve student competency. In conclusion, the development of mobile learning framework provides better understanding and essential for the future of education.